Optimal tuning of PI controller using system identification for two-phase boost converter for low-voltage applications - M. A. N. Amran; A. A. Bakar; M. H. A. Jalil; A. F. H. A. Gani; E. Pathan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper presents modeling and hardware implementations of a two-phase DC-DC boost converter by using the system identification approach. The main objective of this research was to study new methods to obtain the values of the constants for the proportional-integral (PI) controller. Existing methods are time-consuming, since the values of the constants for the PI controller need to be calculated. The system identification approach for the closed-loop boost converter saves more time. This method has the fastest technique to find constants Kp and Ki for the closed-loop two-phase boost converter. To model a two-phase boost converter using the system identification approach, input duty cycle and output voltage are collected in the time domain data. In this study, the transfer function (TF) model, the autoregressive moving average with exogenous (ARMAX) model and the output-error (OE) model were used to generate a mathematical model. To perform the closed-loop analysis, constants Kp and Ki were obtained based on the generated mathematical model from the system identification approach. The result from the experiment shows that the percentages of overshoot for the TF, ARMAX and OE models were 19%, 25.36% and 24.6%, respectively. The output voltage ripples obtained for all three models were less than 5% of output voltage.